Economical 510MPa-grade girder steel belt with thickness of 2.0-10.0 mm and production method thereof
By combining C+Mn+Ti component design and rare earth elements in 510MPa grade beam steel, the adverse impact of liquid TiN on product performance is solved, and the effect of reducing manufacturing costs and improving performance is achieved.
Patent Information
- Application Number
- CN202411564888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-28
AI Technical Summary
The existing 510MPa grade beam steel is prone to precipitation of large-sized TiN during smelting or casting billet cooling, which affects the product's mechanical properties and service safety. In addition, the size and shape of TiN cannot be effectively controlled in traditional methods.
The C+Mn+Ti component design is adopted to cancel the Nb element and reduce the Mn element, improve performance through Ti microalloyation, and reduce the size of liquid-assay TiN and change its shape through rare earth elements, thereby improving product performance and moldability.
It has achieved the reduction of product alloy addition costs, improved yield strength, tensile strength and elongation of beam steel, improved cold forming properties, met customer usage requirements, and reduced adverse effects on product service performance and safety.
Smart Images

Figure CN119530646A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of steel smelting and rolling technology, and specifically relates to an economical 510MPa grade beam steel strip with a thickness of 2.0-10.0mm and a production method thereof. The product of the invention is suitable for the production and manufacture of longitudinal beams, cross beams and structural parts of light, medium and heavy trucks and other commercial vehicles. Background Art
[0002] 510MPa tensile strength beam steel is widely used in the commercial vehicle manufacturing field for processing longitudinal beams, cross beams and their structural parts due to its moderate strength and good plasticity, toughness and formability. Beam steel 510L is a micro-alloyed high-strength steel, which obtains mechanical properties by adding micro-alloying elements and combining corresponding controlled rolling and controlled cooling processes. With the continuous upgrading of steel plant equipment and the increasing maturity of production technology, the traditional Nb-Ti composite micro-alloyed 510L beam steel has no technical threshold, and various large and small steel companies have the production capacity, resulting in increasingly fierce product competition. The application of new processes and new methods to develop a 510MPa beam steel that meets the use requirements and reduces manufacturing costs has become the main development direction of beam steel products.
[0003] The alloy addition cost is an important part of the product manufacturing cost. Reducing the amount of alloy addition by adjusting the composition design is the most effective way to reduce the manufacturing cost. my country is rich in Ti element resources, and has excellent precipitation strengthening and fine grain strengthening effects. It has the potential to develop high-strength steel with a single alloy element and is a microalloying element with extremely high cost performance. The development of single Ti element alloyed 510L beam steel not only has the advantage of low cost, but also reduces the content of Mn and Nb in steel, saves resources, and conforms to the development concept of "green and low carbon". In contrast, single Ti microalloyed products have more Ti elements added, and large-sized TiN is easily precipitated during smelting or billet cooling, which has an adverse effect on the mechanical properties and service safety of the product. Solving the problem of liquid TiN precipitation is the key to the development of single Ti microalloyed high-strength steel. Rare earth elements have the effects of purifying molten steel and modifying inclusions. Rare earth elements form fine rare earth oxides with oxygen and aluminum elements, which can increase the nucleation point of TiN, change the growth mode and shape of TiN, and then reduce the size of TiN, thereby reducing the adverse effect of hard phase TiN in Ti microalloyed steel on product quality. Combining Ti and rare earth elements to develop low-cost controlled automobile beam steel has broad application prospects.
[0004] Patent document CN112030071A discloses a 510MPa grade high-toughness automobile beam steel and a preparation method thereof, which adopts the composition design of C: 0.09-0.11%, Si: ≤0.12%, Mn: 1.00-1.15%, P: ≤0.020%, S≤0.012%, Al: 0.020-0.060%, Ti: 0.040-0.070%, N≤0.0060%, O≤0.0050%, and Re≤0.010% to develop a 1.6-16mm thick Ti micro-alloyed 510MPa grade high-toughness automobile beam steel. The advantage of the method described in this patent is that the use of a single Ti microalloying component reduces the alloy cost of the product; the disadvantage is that when the Ti content is in the range of 0.040-0.070%, large-sized liquid TiN is easily generated, which affects the service performance and service safety of the product. However, the method does not mention or solve the control measures for large-sized TiN. In addition, when the rare earth element content is controlled above 100ppm, continuous casting cannot be achieved in large-scale industrial production of steelmaking, which also increases the product manufacturing cost and is not conducive to large-scale production and promotion.
[0005] Patent document CN103451535A discloses a 510MPa grade hot-rolled strip steel for automobile beams and its production process, which uses C: 0.13-0.18%, Si: 0.30-0.50%, Mn: 0.75-1.15%, P: ≤0.025%, S≤0.008%, Al: 0.020-0.060%, Ti: 0.008-0.025%, N≤0.0060% composition design to develop 1.6-12mm thick Ti micro-alloyed 510MPa grade automobile beam steel, the product yield strength ≥410MPa, tensile strength 515-600MPa, elongation ≥24%, and excellent cold bending performance. The C element and Si content in the method described in the patent are designed to be high, the former will reduce the product welding performance and formability, and the latter will easily cause "red rust" defects on the surface of the steel strip.
[0006] Patent document CN115369307A discloses a method for producing hot-rolled 510L automobile beam steel based on the CSP process. The method adopts C: 0.050-0.070%, Si: 0.03-0.30%, Mn: 0.6-1.2%, P: ≤0.018%, S: ≤0.01%, Nb: 0.01-0.04%, Ti: 0.03-0.06%, N: ≤0.005 composition design based on the CSP process and combines the corresponding controlled rolling and controlled cooling process to develop 510L steel for automobile beams. The product has a yield strength of 450-520MPa, a tensile strength of 550-620Mpa, and an elongation of 24-30%. All indicators meet the standard requirements and the performance control is relatively stable. In the method described in the patent, 0.01-0.04% of Nb elements are added as the main strengthening elements to improve product performance, and the product alloy cost is relatively high. Summary of the invention
[0007] The purpose of the present invention is to provide an economical 510MPa grade beam steel strip with a thickness of 2.0 to 10.0 mm and a production method thereof. The method adopts a C+Mn+Ti composition design, eliminates the Nb element and reduces the Mn element, mainly improves the performance through the Ti microalloying effect, and achieves the purpose of reducing the alloy addition cost of the product. At the same time, rare earth elements are used to reduce the size of the liquid TiN in high-Ti high-strength steel, change the shape of the liquid TiN (from an irregular shape with protruding sharp edges to a round shape), and improve its adverse effects on product performance and forming. The rare earth Ti microalloyed 510MPa grade beam steel has a uniform and refined structure, a yield strength of ≥355MPa, a tensile strength of 510 to 650MPa, an elongation of ≥24%, and good cold formability, meeting customer requirements.
[0008] The specific technical solutions of the present invention are as follows:
[0009] One aspect of the present invention provides an economical 510MPa grade beam steel strip with a thickness of 2.0 to 10.0 mm, whose chemical composition, by mass percentage, is: C: 0.06 to 0.08%, Si: 0.03 to 0.10%, Mn: 0.70% to 1.00%, P≤0.015%, S≤0.005%, Alt: 0.020% to 0.050%, Ti: 0.030% to 0.050%, N≤0.0060%, O≤0.0020%, Ce: 0.0010 to 0.0030%, and the balance is Fe and unavoidable impurities.
[0010] The main elements are selected for the following reasons:
[0011] C: Carbon is a cheap solid solution strengthening element and can also form hard carbides. If the content is too little, alloy elements need to be added to improve product strength, resulting in increased product manufacturing costs. If the content is too much, it will affect product forming, welding performance, impact performance and fatigue performance. This product is mainly used for processing automobile beams. It needs to have good plasticity and cold forming performance during processing. In addition to strength, it also needs to have impact toughness and fatigue resistance during service. Taking comprehensive considerations, its content is limited to 0.06-0.08%.
[0012] Si: Silicon is a deoxidizing element and has a good solid solution strengthening effect. However, if the Si content is too high, it will easily cause red oxides to form on the surface of the steel strip. The product processing beam has a painting process. If the Si content is high, it will affect the appearance of the product. Considering comprehensive considerations, its content is limited to 0.03-0.10%.
[0013] Mn: Manganese can be infinitely substituted with iron for solid solution, and is the most cost-effective solid solution strengthening element after C. However, if the Mn content is too high, it is easy to cause slab segregation, which is inherited to the finished product to form a harder center segregated pearlite banded structure. This problem is more serious, especially for thick specifications. The compression ratio is small and the cooling rate at the center of the thickness is low. The pearlite banded structure seriously deteriorates the formability and fatigue properties of the product. Considering all factors, its content is limited to 0.70% to 1.00%.
[0014] P, S: Phosphorus and sulfur are unavoidable harmful elements in steel. The lower their content, the better the product performance. However, too low a control will increase production costs. Taking comprehensive consideration, their contents are limited to P≤0.015% and S≤0.005% respectively.
[0015] Alt: Aluminum is added for deoxidation. When the aluminum content is insufficient, it cannot exert its effect. When the aluminum content is too high, the ductility deteriorates. Considering all factors, its content is limited to 0.020% to 0.050%.
[0016] Ti: Titanium has the effects of grain refinement and precipitation strengthening. Grain refinement is mainly achieved by fine TiN inhibiting the growth of high-temperature austenite grains, and precipitation strengthening is mainly achieved by precipitating fine TiC between phases or on the ferrite matrix to hinder dislocation movement. The comprehensive product performance requirements limit its content to 0.030-0.050%.
[0017] O: Titanium is chemically active and reacts with O first to produce compounds. The more O content in steel, the more Ti is consumed, which reduces the effective titanium content for γ→α phase transformation or precipitation of TiC on the ferrite matrix, weakening the precipitation strengthening effect of titanium. Taking all factors into consideration, its content is limited to ≤0.0060%.
[0018] N: Titanium is chemically active and reacts with N first to form compounds. The higher the N content in steel, the more Ti is consumed. On the one hand, the effective titanium content for TiC precipitation in the γ→α phase transformation or on the ferrite matrix is reduced, weakening the precipitation strengthening effect of titanium; on the other hand, the TiN formed during the smelting process is large in size and has sharp edges, which has an adverse effect on performance. However, controlling the N element requires increasing the smelting cost, and considering comprehensively, its content is limited to ≤0.0020%.
[0019] Ce: Rare earth Ce has active chemical properties. When rare earth is added to steel, fine CeAl 2 O 3The production of composite oxide increases the nucleation point of TiN and changes the aggregation mode of Ti and N, thereby reducing the size and shape of TiN, which helps to improve the adverse effect of TiN in Ti-containing steel on product performance. Taking into account the role of rare earth Ce and the smooth progress of industrial production, the Ce content in steel is controlled at 0.0010-0.0030%.
[0020] In some embodiments, the mechanical properties of the beam steel strip meet the following requirements: yield strength ≥ 460 MPa, tensile strength ≥ 530 MPa, and elongation A ≥ 30%.
[0021] In some embodiments, the thickness of the beam steel strip is 3.0-6.0 mm.
[0022] In some embodiments, the chemical composition of the beam steel strip is calculated by mass percentage: C: 0.07%, Si: 0.08-0.09%, Mn: 0.92%-0.95%, P≤0.015%, S≤0.005%, Alt: 0.02%-0.03%, Ti: 0.038%-0.040%, N≤0.0050%, O≤0.0020%, Ce: 0.0015-0.0018%, and the balance is Fe and unavoidable impurities.
[0023] Another aspect of the present invention provides a method for producing a beam steel strip, which includes a steelmaking process and a controlled rolling air cooling process.
[0024] In some embodiments, the steelmaking process includes: KR desulfurization, converter, LF refining and slab continuous casting; wherein the molten iron needs to be deeply desulfurized, the molten iron S after desulfurization is ≤0.002%, the slag is removed after desulfurization, and the slag removal area (bright surface) is greater than 90%; the converter tapping process requires the use of normal turnover ladles, and the use of new ladles and black ladles is strictly prohibited, and the amount of slag removed during tapping is strictly controlled; aluminum iron is used for deoxidation of converter tapping, and lime and synthetic slag are used for slag adjustment; the amount of aluminum iron and slag added is adjusted according to the end point C content; in the early stage of LF refining and when adjusting the composition, appropriate argon blowing intensity is used for stirring (the molten steel is not overturned and exposed); when power is supplied 1. During the refining process, add appropriate amount of aluminum particles to strengthen slag surface deoxidation, and control the Als of the second sample of LF ≥ 0.050%; no ferrosilicon is added during the LF refining process; according to the in-situ sulfur content, add lime to adjust the refined slag in time, and ensure good fluidity of the refined slag, the final refining slag (FeO) + (MnO) ≤ 0.5% and the white slag retention time ≥ 20 minutes; feed pure calcium wire during the calcium treatment process, and the calcium content of the molten steel is required to be 0.0008-0.0020%; after calcium treatment, add 20-40kg of cerium iron alloy and soft blow for 5 minutes. It is required that the slag surface has only slight fluctuations during soft blowing to ensure the soft blowing effect and prevent the steel liquid from being exposed.
[0025] In some embodiments, the controlled rolling and air cooling process adopts a 2250mm hot rolling mill, including: slab (continuous casting slab thickness is 230mm) heating, rough rolling, finish rolling and steel coil cooling; wherein:
[0026] The heating of the slab should consider both the full solid solution of the alloy elements and the prevention of excessive grain coarsening. Therefore, the heating temperature of the slab is controlled at 1240-1255℃, and the soaking time is controlled at 20-30min.
[0027] The slab temperature is high during the rough rolling stage and is in the complete recrystallization zone. It is an important process for refining the coarse grains of the slab and a key link in achieving uniformity of the product thickness. The two necessary conditions for using recrystallization to refine the grain size are high temperature and large deformation. Therefore, the rough rolling of the slab adopts 3+3 rolling for a total of 6 passes, and the reduction of the first pass is controlled at 35-40mm.
[0028] In the finishing rolling stage, the partial recrystallization zone is avoided, and rolling is controlled in the non-recrystallization zone. The partial recrystallization zone is prone to mixed crystal structure, and the thickness center problem is more serious. Rolling in the non-recrystallization zone can lengthen the grain size, increase the grain boundary area, and provide more nucleation points for subsequent phase transformation, thereby achieving the purpose of refining the grain size. Increasing the reduction in the finishing rolling stage and the lower final rolling temperature are also helpful to increase the grain boundary area and nucleation points. Therefore, the intermediate billet temperature is controlled at ≤960℃, the intermediate billet thickness is controlled at 55-65mm, and the final rolling temperature is controlled at 800-820℃.
[0029] If the cooling speed of the steel coil is too slow, the size of the refined grains will grow. If the cooling speed is too fast, the "red return" problem will occur. In order to eliminate such problems, the cooling speed is controlled at 15-25℃ / s, and the coiling temperature is mainly considered to be the optimal temperature for TiC precipitation, which is controlled at 580-600℃.
[0030] The special feature of the technical solution of the present invention is that the method successfully develops an economical 510MPa grade beam steel by using a single Ti microalloying method and reasonably setting its content in combination with a corresponding controlled rolling and controlled cooling process, and at the same time utilizes rare earth elements to modify the liquid TiN inclusions in the steel, thereby reducing their adverse effects on the service performance and safety of the product.
[0031] Beneficial effects:
[0032] 1. The 510MPa-grade beam steel manufacturing method provided by the present invention reduces the manufacturing cost of the product and improves the product's profit-making ability. The market demand for 510MPa-grade beam steel is still strong, which can create objective economic benefits for the enterprise.
[0033] 2. Ti is the most cost-effective fine-grain strengthening element and has great advantages in the development of microalloyed high-strength steel. The application of rare earth in the present invention solves the technical problem that the liquid TiN in Ti microalloyed high-strength steel seriously harms the performance and safety to a certain extent. The disclosed technology of combining Ti and rare earth application will become the development direction of low-cost controlled microalloyed high-strength steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The metallographic structures at the 1 / 4 (a) and 1 / 2 (b) positions in the thickness direction of the steel strip of the embodiment of the present invention are shown. The product is mainly composed of polygonal ferrite, with fine and uniform grains and a grain size rating of 10.5. DETAILED DESCRIPTION
[0035] The present invention is described in detail below through specific examples. The examples are intended to help understand the present invention but are not intended to limit the present invention.
[0036] Specifically, the present invention provides an economical 510MPa grade beam steel strip with a thickness of 2.0 to 10.0 mm, whose chemical composition is as follows by mass percentage: C: 0.06 to 0.08%, Si: 0.03 to 0.10%, Mn: 0.70% to 1.00%, P≤0.015%, S≤0.005%, Alt: 0.020% to 0.050%, Ti: 0.030% to 0.050%, N≤0.0060%, O≤0.0020%, Ce: 0.0010 to 0.0030%, and the balance is Fe and unavoidable impurities.
[0037] The production method provided by the present invention includes a steelmaking process and a controlled rolling air cooling process; wherein:
[0038] The steelmaking process includes: KR desulfurization, converter, LF refining and slab continuous casting; the molten iron needs to be deeply desulfurized, and the S of the molten iron after desulfurization is ≤0.002%. After desulfurization, the slag is removed, and the slag removal area (bright surface) is greater than 90%; the converter tapping process requires the use of normal turnover ladles, and it is strictly forbidden to use new ladles and black ladles, and the amount of slag discharged during tapping is strictly controlled; aluminum iron is used for deoxidation during converter tapping, and lime and synthetic slag are used for slag adjustment; the amount of aluminum iron and slag added is adjusted according to the end C content; in the early stage of LF refining and when adjusting the composition, appropriate argon blowing intensity is used for stirring (the molten steel is not overturned and exposed); in the power transmission and refining process In the process of LF refining, add appropriate amount of aluminum particles to strengthen slag surface deoxidation, control LF second sample Als ≥ 0.050%; no more ferrosilicon is added during LF refining; according to the in-situ sulfur content, add lime to adjust the refined slag in time, and ensure good fluidity of the refined slag, the final refining slag (FeO) + (MnO) ≤ 0.5% and the white slag retention time ≥ 20 minutes; feed pure calcium wire during calcium treatment, and the calcium content of molten steel is required to be 0.0008-0.0020%; after calcium treatment, add 20-40kg cerium iron alloy and soft blow for 5 minutes. It is required that the slag surface has only slight fluctuations during soft blowing to ensure the soft blowing effect and prevent the steel liquid from being exposed.
[0039] The controlled rolling air cooling process includes: slab heating, rough rolling, finishing rolling and coil cooling; wherein: the slab heating temperature is controlled at 1240-1255°C, and the soaking time is controlled at 20-30min; the slab rough rolling adopts 3+3 rolling for a total of 6 passes, and the increase in the first pass reduction is controlled at 35-40mm; in the finishing rolling stage, the intermediate billet temperature is controlled at ≤960°C, the intermediate billet thickness is controlled at 55-65mm, and the final rolling temperature is controlled at 800-820°C; the coil cooling rate is controlled at 15-25°C / s, and the coiling temperature is controlled at 580-600°C.
[0040] In order to further understand the present invention, two groups of 510MPa grade beam steel strip embodiments of the present invention are provided. The chemical composition control of the embodiments is shown in Table 1, the heating-rolling-cooling parameter control of the embodiments is shown in Table 2, and the mechanical properties of the embodiments are shown in Table 3.
[0041] Table 1: Chemical composition of example steel (wt%)
[0042] Example C Si Mn P S Ti Alt N Ce 1 0.07 0.09 0.92 0.011 0.003 0.038 0.02 0.0046 0.0015 2 0.07 0.08 0.95 0.013 0.004 0.040 0.03 0.0045 0.0018
[0043] Table 2: Example steel process system
[0044]
[0045] Table 3: Mechanical properties of steel in the examples
[0046]
[0047] It can be seen from the examples that the yield strength, tensile strength and elongation of the steel strip of the examples of the present invention all meet the requirements of the national standard GB / T3273, especially the elongation margin is large, so that the product has good cold formability.
[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An economical 510MPa grade beam steel strip with a thickness of 2.0 to 10.0 mm, characterized in that: The chemical composition of the beam steel strip is calculated by mass percentage as follows: C: 0.06%-0.08%, Si: 0.03%-0.10%, Mn: 0.70%-1.00%, P≤0.015%, S≤0.005%, Alt: 0.020%-0.050%, Ti: 0.030%-0.050%, N≤0.0060%, O≤0.0020%, Ce: 0.0010%-0.0030%, and the balance is Fe and unavoidable impurities.
2. The beam steel belt according to claim 1, characterized in that: The mechanical properties of the beam steel strip meet the following requirements: yield strength ≥460MPa, tensile strength ≥530MPa, and elongation A ≥30%.
3. The beam steel strip according to claim 1 or 2, characterized in that: The thickness of the beam steel strip is 3.0-6.0 mm.
4. The beam steel strip according to any one of claims 1 to 3, characterized in that: The chemical composition of the beam steel strip is calculated by mass percentage as follows: C: 0.07%, Si: 0.08-0.09%, Mn: 0.92%-0.95%, P≤0.015%, S≤0.005%, Alt: 0.02%-0.03%, Ti: 0.038%-0.040%, N≤0.0050%, O≤0.0020%, Ce: 0.0015-0.0018%, and the remainder is Fe and unavoidable impurities.
5. The method for producing a beam steel strip according to any one of claims 1 to 4, characterized in that: The production method comprises a steelmaking process and a controlled rolling air cooling process.
6. The production method according to claim 5, characterized in that The steelmaking process includes: KR desulfurization, converter, LF refining and slab continuous casting; wherein the molten iron needs to be deeply desulfurized, the molten iron S after desulfurization is ≤0.002%, the slag is removed after desulfurization, and the slag removal area (bright surface) is greater than 90%; the converter tapping process requires the use of normal turnover ladles, and it is strictly forbidden to use new ladles and black ladles, and the amount of slag removed during tapping is strictly controlled; aluminum iron is used for deoxidation during converter tapping, and lime and synthetic slag are used for slag adjustment; the amount of aluminum iron and slag added is adjusted according to the end point C content; in the early stage of LF refining and when adjusting the composition, appropriate argon blowing intensity is used for stirring (the molten steel is not overturned and exposed); in the power transmission and refining process During the process, add appropriate amount of aluminum particles to strengthen slag surface deoxidation, control LF second sample Als ≥ 0.050%; no ferrosilicon is added during LF refining; according to the in-situ sulfur content, add lime to adjust the refined slag in time, and ensure good fluidity of the refined slag, the final refining slag (FeO) + (MnO) ≤ 0.5% and the white slag retention time ≥ 20 minutes; feed pure calcium wire during calcium treatment, and the calcium content of molten steel is required to be 0.0008-0.0020%; add 20-40kg cerium iron alloy after calcium treatment, and soft blowing for 5 minutes, requiring that the slag surface has only slight fluctuations during soft blowing to ensure the soft blowing effect and prevent the steel liquid from being exposed.
7. The production method according to claim 5 or 6, characterized in that: The controlled rolling and air cooling process includes: slab heating, rough rolling, finish rolling and coil cooling; wherein: The slab heating temperature is controlled at 1240-1255°C, and the soaking time is controlled at 20-30 minutes; The rough rolling of slab adopts 3+3 rolling, a total of 6 passes, and the reduction of the first pass is controlled at 35-40mm; In the finishing rolling stage, the intermediate billet temperature is controlled at ≤960℃, the intermediate billet thickness is controlled at 55~65mm, and the final rolling temperature is controlled at 800~820℃; The cooling rate of the steel coil is controlled at 15-25°C / s, and the coiling temperature is controlled at 580-600°C.
Citation Information
Patent Citations
Hot continuous rolling plate strip steel for 510MPa automotive frame and production technology thereof
CN103451535A
510MPa-grade high-toughness automobile girder steel and preparation method thereof
CN112030071A
Manufacturing method for producing hot-rolled 510L automobile beam steel based on CSP process
CN115369307A
Automobile beam steel with tensile strength of 550MPa and preparation method for automobile beam steel
CN104805358A
500MPa-grade high-strength steel and preparation method thereof
CN112301275A